Social and psychological adaptation features of newly appointed managers - A. A. Avdeeva; M. V. Iontseva (Вестник университета, 2022)
In the professional environment, socio-psychological adaptation to work occurs among workers, ordinary specialists and managers. The adaptation process is the most difficult for employees appointed to a managerial position for the first time. This is because they need not only to adapt to a new job, but also to choose a suitable management strategy, as well as to meet the expectations of subordinates and match their level. They should have such managerial skills to set correctly tasks taking into account the professional level of subordinates and their socio-psychological characteristics. The authors of the article consider the main problems faced by first-time managers during the socio-psychological adaptation to professional activity. The study presents the most effective mechanisms and tools that will make the adaptation of such employees as successful as possible.